Abeghyan’s Interpretation of Verb Moods in Eastern Armenian, Considered from the Viewpoint of Modern Linguistics - Avetyan, Sargis (Bulletin of Yerevan University B: Philology, 2024)
It is argued that the traditional interpretation (proposed by M. Abeghyan) of the so-called Optative mood (ըղձական եղանակ) and Hypothetical/Conditional mood (ենթադրական/պայմանական եղանակ) in Modern Eastern Armenian, is objectionable from the standpoint of General Linguistics and Linguistic Typology. The point is that the Optative of Modern Eastern Armenian combines most of the semantic functions of the typologically known Subjunctive and Optative. Therefore, it is not an Optative in the proper sense of the word. It would be more appropriate to characterize it as Subjunctive-Optative (ստորադասաըղձական). As to the կ(ը)- future (traditionally misinterpreted as Hypothetical/Conditional mood), it is actually no different from the Future Indicative in other languages from the semantic-functional point of view. As pointed out by a number of scholars, the future tense is never a purely temporal category; futurity necessarily includes an element of prediction or some related modal notion. Accordingly, the կ(ը)- future in Modern Eastern Armenian also includes both temporal and modal semantic components, the proportion of which may vary depending on the specific context and the person of the verb form. However, the corresponding past forms of the կ(ը)- future mainly function as Conditional in Modern Eastern Armenian.